(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Job satisfaction is one of the most widely discussed issues inorganizational behavior, personnel and uman resource management and organizationalmanagement. As teaching does require a great deal of thoroughness andcommitment, so in teaching it is more important to have mental commitment andloyalty than physical presence. In this study the researcher investigated thepresent level of job satisfaction among the faculty members of university ofHyderabad. The major purpose of this descriptive-correlational study was toexamine factors affecting job satisfaction of faculty members of University ofHyderabad which is explained by Herzberg job motivator and hygiene factors. Arandom sample of 120 faculty member of Hyderabad University was selected as astatistical sample. Employing a descriptive-correlative survey method and datawere collected through questionnaire. The faculty members were generallysatisfied with their jobs. However, male faculty members were less satisfiedthan female faculty members. The factor “work itself” was the most motivatingaspect for faculty. The least motivating aspect was “working conditions.” Thedemographic characteristics were negligibly related to overall jobsatisfaction. The factors “work itself,” and “advancement” explained 60 percentof the variance among faculty members’ overall level of job satisfaction. Thedemographic characteristics (age, years of experience, academic rank, degree)were negligibly related to overall job satisfaction.